Iklan
Iklan

f(x) = -x² + 2x + 3

_____________________________

Penjelasan dengan langkah-langkah:

y = ax² + bx + c

x = 0 → c = 3

x = -1 → a - b + c = 0

x = 3 → 9a + 3b + c = 0

Sederhanakan,

  • a - b = -3 <=> a = -3 + b
  • 9a + 3b = -3

Substitusikan persamaan a,

9a + 3b = -3

9(-3 + b) + 3b = -3

3(-3 + b) + b = -1

-9 + 3b + b = -1

4b = 8

b = 2

Substitusi b ke persamaan a,

a = -3 + b

a = -3 + 2

a = -1

Bentuk fungsi kuadrat,

f(x) = ax² + bx + c

f(x) = -x² + 2x + 3

Iklan
Iklan